Linguistic analysis of hate speech on social networks - Ramírez Salado, Mercedes (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Hate speech is currently becoming a field of interest for different academic domains, which is why in this contribution a linguistic approach to this type of messages is presented. For that purpose, a corpus of almost a hundred texts from social networks has been examined, describing the linguistic features of this type of messages and explaining their relevance for forensic linguistics.